A LINGUISTIC LANDSCAPE ANALYSIS OF ISLAMIC BOARDING SCHOOLS IN EAST BANDUNG - Jefira Setia Aini; Agus Karim; Muhammad Ibnu Pamungkas (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates verbal and visual semiotics in the linguistic landscape of Islamic boarding schools (pesantren) in East Bandung, Indonesia, examining how public signs are used to construct and project institutional identity. Using qualitative semiotic analysis of photographs and textual data, this study examines how verbal and visual signs construct meaning in the school environment. The research draws on data collected through participatory observation, photographic documentation, and interviews in four case-study institutions: Al-Mu’awanah, Ma'had Al-Jami'ah, Al-Mahad Al-Lughawi, and Al-Ihsan. The signs, including signboards, banners, and logos, were analyzed using Landry and Bourhis’s linguistic landscape framework and Charles Sanders Peirce’s semiotic model. The analysis reveals three dominant semiotic functions: reinforcement of religious identity, regulation of institutional authority, and integration of visual and verbal codes in daily school life. Each pesantren strategically cultivates a distinct identity through its linguistic landscape, ranging from a balance between tradition and modernity to “progressive traditionalism” that blends classical religious aesthetics with modern corporate branding. This study is among the first to examine the linguistic landscape of Islamic boarding schools in Indonesia, showing how semiotic practices in these religious educational spaces reflect broader cultural and institutional dynamics. The findings contribute to semiotic and linguistic landscape scholarship by demonstrating how verbal and visual signs in religious institutions construct identity and authority. This study underscores the importance of analyzing linguistic landscapes in religious educational settings to understand how semiotics mediates identity, authority, and cultural continuity.